Corporate Social Responsibility (CSR) dan Reputasi Perusahaan - Wahidatul Husnaini; Elin Erlina Sasanti; Susi Retna Cahyaningtyas (Jurnal Aplikasi Akuntansi, 2018)
Unethical and irresponsibilty behaviour has recently led to an increasing popularity of Corporate Social Responsibility (CSR) worldwide. CSR is considered not only focusing on the right business but also emphasizing the business responsibility for dynamic environmental change. The reputation of companies that engage in CSR activities will likely improve in the eyes of stakeholders as stakeholders obtain information regarding the company's activities or products presented in the CSR report, which in turn could indirectly affects the reputation. This study aims to analzye whether the CSR activities carreid out by the company will improve reputation. Research sample consists of 36 non banking and financial institution company listed in Indonesian Stock Exchange (BEI) period 2013-2015 who was declared as winner of Sustainability Report Award (SRA) 2016. The result of hypothesis testing based on simple linear regression indicate that CSR has negative effect to company reputation.